PENGARUH KECEMASAN MATEMATIKA TERHADAP PERSIAPAN TES UTBK SISWA SMAN 1 KEFAMENANU - Laja, Yosepha Patricia Wua; Simarmata, Justin Eduardo (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2022)
Math anxiety is a condition that inhibits students' ability to reach the potential of learning experiences and classroom math assessments, or both which are emotional responses and objects of fear or fear. This definition shows that math anxiety can be one of the internal factors felt by each individual, especially when approaching certain tests or exams. UTBK test is one type of test or exam that makes math a compulsory subject that is tested. Students need to be given preparation in the form of guidance to reduce math anxiety in order to get maximum results. The purpose of this study is to see if there is an influence between math anxiety on UTBK test preparation of SMAN 1 Kefamenanu students. The method used in this research is descriptive quantitative. The population of this study were all students of SMAN 1 Kefamenanu Class XII. While sampling was done randomly totaling 71 students. The results showed that there was a negative relationship between math anxiety and UTBK test preparation results (simulation). However, this relationship does not have a significant effect on the result of UTBK test preparation